An Integrated Computational and Laboratory Approach for Selective Amplification of mRNAs Containing the Adenylate Uridylate-Rich Element Consensus Sequence - Khabar, Khalid S.A.; Dhalla, Mohammed; Bakheet, Tala; Sy, Cheikh; al-Haj, Latifa

(untitled) (Genome Research, 2002)
Messenger RNAs that have the stability determinants, adenylate uridylate-rich elements (AREs), in their 3′ untranslated region (UTR) code for key products that regulate early and transient biological responses. We used a computational laboratory approach for amplification of large, including full-length, protein-coding regions for ARE genes. Statistical analysis of the initiation regions in the 5′ UTR of ARE-mRNAs was performed. Accordingly, several 5′ primers and a single universal 3′ primer that targeted the initiation consensuses and ARE regions, respectively, were designed. Using optimized conditions, the primers were able to enrich and amplify large protein-coding regions for the ARE gene family. The selective amplification of ARE cDNAs was verified using specific polymerase chain reactions (PCRs) to known ARE mRNA molecules and monitoring the abundance of the non-ARE β-actin signal. A mini-library from the amplified ARE products was constructed for further confirmation of ARE selection. Distinct ARE amplified cDNA pools were selectively generated by distinct 5′ primers. The biological utility of the method was shown with differential display. The up-regulation of several ARE-mRNAs, including the full-length coding region of the small inducible cytokine A4 (SCYA4) gene, was shown in endotoxin-stimulated monocytic cells. The integrated computational and laboratory approach should lead to enhanced capability for discovery and expression analysis of early and transient response genes.